The Effect of the Reflective Pedagogy Paradigm Approach in Improving the Disciplinary Attitudes of Third Grade Students of SD Inpres Bontoala I Gowa Regency - Musdalifah Syahrir; Tasya Regita Cahyani; Muhajir Muhajir; Andi Sugiati; Rismawati Rismawati (JED (Jurnal Etika Demokrasi), 2023)
In terms of obeying the rules, students in uniform, whether according to the regulations, clothes are inserted, and wear a belt and black shoes. The researcher also observed students' self-control and whether students listened when the teacher explained. Another thing that was observed was students' awareness when learning, whether they worked seriously to get good grades. Interviews conducted by researchers with class teachers related to student discipline in participating in learning at school. The type of research used is quantitative research. This means that this research aims to find data through experiments. The experiment format chosen in this research is a pre-experimental design. It is said to be a pre-experimental design because the design is not a real experiment because external variables will still affect the formation of the dependent variable. The subject and research sample are class III students totaling 33 people. Data collection techniques include initial tests, treatment, and final tests. The data used in this study are descriptive statistical analysis and inferential statistical data analysis. From the results of the calculation on the pretest, the average value of the discipline level of the students of SD Inpres Bontoala I, Pallangga District, Gowa Regency, after using the Reflective Pedagogy Paradigm Approach is 60.45. And from the posttest calculation, the average value of the discipline level of SD Inpres Bontoala I students in Pallangga District, Gowa Regency, after using the Reflective Pedagogy Paradigm Approach is 84.54.